(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The term Web 2.0 was coined in 2004 by Dale Dougerthy of the publishing house O’Reilly in a session of brainstorming. Though it was the article “ What is Web 2.0?“ written by Tim O’Reilly, CEO of the above mentioned publishing house, the point of item of the explosion that has produced to it self in the latter five years concerning this one already very popular term of Web 2.0. In 2006, MaCafee, teacher of Harvard’s University, he used, also for the first time, in an article, the term Enterprise 2.0, to say to the strategies that they had to follow the enterprises to use the social software. The article analyzes the concept of social Web, your technology associated (blogs, wikis, podcast, RSS, Social Networks,…) and he propos esstrategies to continuing for the companies for the implantation of the social Web.The concept Enterprise 2.0 appears as a new model of organization and of corporate culture and it needs of strategies to incorporate and to use efficiently the technologies Web 2.0, that shape the Social Web, to the business and current and futureenterprise -specially- of next decade.